The effect of competence, implementation of government accounting standards and financial accounting systems on accountability of regional financial management with the quality of financial reports as a moderation variable - SAYIDAH MARYAM SINOSI; SYARIFUDDIN; ANDI KUSUMAWATI (International Journal of Multidisciplinary Research and Studies, 2023)
This study aims to examine and analyze the influence of competence, implementation of government accounting standards, and financial accounting systems on regional financial management accountability with the quality of financial reports as a moderating variable. The population in this study were financial employees at the SKPD in Soppeng Regency as many as 26 SKPD with a total of 108 financial employees. The type of sample used is a saturated sample because all populations are sampled. Data analysis used descriptive statistical analysis, classical assumption test, and research hypothesis test. The results of the study show (1) competence has no effect on regional financial management accountability, (2) implementation of accounting standards has no effect on regional financial management accountability, (3) financial accounting systems have an effect on regional financial management accountability, (4) financial report quality can moderate the effect of competency on regional financial management accountability, (5) the quality of financial reports can moderate the effect of implementing government accounting standards on regional financial management accountability, (6) the quality of financial reports can moderate the effect of the financial accounting system on regional financial management accountability